Paradigm Shift in Orientalism (A Study of the Thoughts of Contemporary Orientalist Figures) - Andika; Br Surbakti, Junita; Meor Johari, Meor Muhammed Afique (LP2M IAIN Palopo, 2025)
This article aims to analyze the paradigm shift in the study of orientalism through the thoughts of contemporary orientalists such as Karen Armstrong, Annemarie Schimmel, Martin Lings, John Obert Voll, and Charles Kurzman. This article attempts to show how their approaches correct the bias of classical orientalists by offering a more sympathetic, holistic, and internally based perspective on Islam. This research uses a qualitative approach through literature studies with descriptive analysis methods. This study finds that the paradigm shift from classical to contemporary orientalism was triggered by historical, religious, political, cultural, and intellectual factors after the end of colonialism. These contemporary orientalists emerged and brought major contributions such as a humanist approach that emphasizes an empathetic narrative of Islam, a deep spiritual and esoteric understanding of Islam, and a critical analysis of the dynamics of contemporary Islam in responding to modernity and democracy. Together, they challenge the stereotype of classical orientalism by showing the diversity, depth, and relevance of Islam in a global context. This article concludes that the thoughts of contemporary orientalists have represented a new generation of Islamic studies in the West that is fairer and more objective. They not only correct the misperceptions of past orientalism, but also pave the way for a more productive dialogue between Islam and the West. Keywords: Contemporary Orientalism; Classical Orientalism; Paradigm Shift.